Podręcznik tradycyjny czy e-learning? Wybór podręcznika kursowego na lektorat akademicki z języka polskiego jako obcego (na przykładzie polonistyki włoskiej) - Jakobsze, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The primary aim of the article was a reflection on the choice of a coursebook for the Polish language course at Italian universities. The first part of this paper describes the specifics of Polish studies in Italy and focuses on conditions influencing the choice, such as: the profile of the student, type of course and the educational context. The second part presents classifications of manuals used for Polish language courses in Italy. This classifications are accompanied by a list of criteria which help to select some particular groups of manuals. The secondary aim of the article, which is presented in the last part, was to introduces an e-learning platform E-LOCAL supporting a Polish language teaching as an alternative, modern and customizable coursebook.